Nanoscale silicon surface-assisted laser desorption/ionization mass spectrometry: environment stability and activation by simple vacuum oven desiccation. Issue 16 (17th June 2016) - Tsao, Chia-Wen; Lin, Yuan-Jing; Chen, Pi-Yu; Yang, Yu-Liang; Tan, Say Hwa
Abstract : Environmental (air, inert gas, vacuum) stability and vacuum oven desiccation for high sensitivity nanoscale silicon SALDI-MS is investigated. Abstract : Nanoscale silicon surface-assisted laser desorption/ionization mass spectrometry (SALDI-MS) is an emerging matrix-free, highly sensitive MS analysis method. An important challenge in using nanoscale silicon SALDI-MS analysis is the aging and stability of silicon after storage in various environments. No proper nanoscale silicon SALDI-MS activation procedure has been reported to solve this issue. This study investigated the sensitivity, wettability, and surface oxidation behavior of nanoscale silicon surface SALDI-MS in a room, an inert gas atmosphere, and a vacuum environment. A simple vacuum oven desiccation was proposed to activate the SALDI-MS surface, and the limit of detection was further enhanced 1000 times to a 500 attomole level using this approach. The long-term stability and desorption/ionization mechanism were also investigated.